A Study on Consumption and Characterization of Stabilizer Content of NEPE Propellant via FTIR. Issue 7 (25th April 2019) - Tao, Tao; Sui, Xin; Li, Shipeng; Wang, Ningfei
Abstract: Nitrate ester plasticised polyether (NEPE) propellants, a kind of high‐energy solid propellant, were tested for their stabilizer content and Fourier transform infrared spectrum (FTIR) to study their ageing performance. On the one hand, a stabilizer consumption equation containing the ageing temperature, stabilizer content, and ageing time was established by analyzing the data of stabilizer content of NEPE aged at high temperatures (328, 333, 338, 343, 348, and 353 K). On the other hand, it was found that the second derivative spectral absorbance of 1598 cm −1 has a high linear correlation to the stabilizer content of NEPE propellant, and an equation, which can be used to calculate the stabilizer content of NEPE with FTIR data, was established. Thereafter, to prove the universality and accuracy of these two equations, FTIR testing of NEPE aged at room temperature (298 K) was carried out. Accordingly, the two other equations for stabilizer consumption at room temperature were derived by the FTIR data and the stabilizer consumption equation, respectively. They were consistent and the universality and accuracy of these equations were proven, and the feasibility of non‐destructive monitoring methods for NEPE propellants via FTIR was experimentally verified. Abstract :